Razrabotka i vnedrenie sistemy sudejstva sorevnovanij po figurnomu kataniju na kon'kach dlja detej s rasstrojstvami autisticeskogo spektr - Sopov, V. F.; Shakirova, A. V.; Gubanov, A. M. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article discusses the organizational and methodological features of the competition for children with autism spectrum disorders (ASD). The author`s development of an alternative judging system for figure skating based on the existing international judging system (ISU) in combination with a behavioral assessment, which is an important criterion for tracking the dynamics of the psychophysical development of students, is presented and tested. The role of competitions in the social adaptation of children with mental disorders is reflected.Keywords: adaptive sports, figure skating, autism, autism spectrum disorder (ASD), psychophysical development of children, mental disorders, competitions.